Comparative Analysis of Pedagogical Approaches for Enhancing Proficiency in Turkish Language among International Learners - Karimova Rayhona (Euro Asian Journal Publishing, 2024)
This research aims to provide valuable insights into the most effective pedagogical approaches for teaching Turkish to international learners. By comparing various methods and strategies, the study seeks to identify best practices that can enhance language proficiency and support the diverse learning needs of non-native speakers. The findings are expected to contribute to the development of more targeted and impactful language teaching programs for Turkish learners from different linguistic and cultural backgrounds.
Keywords: Comparative analysis; pedagogical approaches; proficiency